2016
DOI: 10.2215/cjn.12971215
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of the Cubilin (CUBN) and Megalin (LRP2) Genes with ESRD in African Americans

Abstract: Background and objectives Genetic variation in the cubilin (CUBN) gene is associated with albuminuria and CKD. Common and rare coding variants in CUBN and the gene encoding its transport partner megalin (LRP2) were assessed for association with ESRD in blacks.Design, setting, participants, & measurements Sixty-six CUBN and LRP2 single-nucleotide polymorphisms (SNPs) were selected and analyzed in this multistage study. Exome sequencing data from 529 blacks with type 2 diabetes (T2D) -associated ESRD and 535 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The presence of at least one C-allele was recently described to be a risk factor for ESRD in African Americans [9]. In the present study, we also found evidence of such association for a Caucasian cohort of T2D patients.…”
Section: Interpretation Of Findings In Relationship Withsupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of at least one C-allele was recently described to be a risk factor for ESRD in African Americans [9]. In the present study, we also found evidence of such association for a Caucasian cohort of T2D patients.…”
Section: Interpretation Of Findings In Relationship Withsupporting
confidence: 87%
“…In accordance with previous studies where carriers of at least one CUBN (rs1801239) C-allele were at increased risk for ESRD [9] or proteinuria [8], we hypothesized that such patients would showcase a similar pattern in our cohort.…”
Section: Key Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…Of the 4 loci found to be genome-wide significant in the present study (discovery phase), the locus on chr 17 have already been reported in East Asians, whereas other 2 loci on chr 2 and 18 are first reported in the East Asian and Japanese populations. However, they were reported in the GWAS of ­renal traits in European populations and/or those with African ancestries, as represented by the LRP2 locus on chr 2 in African Americans [21, 39]. To the best of our knowledge, the association of the 4q23 locus with CKD risk is the novel finding, which warrants further investigations with independent data sets.…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that genetic factors may play a role in the development of nephropathy and ESKD in T2D patients. While the apolipoprotein L1 gene ( APOL1 ) explains a substantial proportion of the disparity in non-diabetic ESKD in AAs (Tzur et al 2010; Genovese et al 2010), less is known about the genetic contributors to the high T2D-ESKD risk in AAs (Bonomo et al 2014a; Ma et al 2016; Skorecki and Wasser 2016). …”
Section: Introductionmentioning
confidence: 99%